IMPACT OF LAISSEZ-FAIRE, TRANSACTIONAL AND TRANSFORMATIONAL LEADERSHIP - Rajbanshi, Bijendra (JBFEM, 2020)
While the concept of leadership has been extensively explored, there is limited research investigating which leadership style is good for employees to increase their motivation level in the ICT sector. This research explores the impact of Laissez-faire, Transactional and Transformational leadership styles on the motivation of employees in the ICT sector in Nepal in quantitative methods. The survey questionnaire method was chosen for the data collection. Data were collected from 45 employees working in 5 different ICT companies inside the Kathmandu Valley, where they responded about the head of their organization’s leadership style and their level of motivation. Convenience sampling was used. This research used multiple linear regression analysis to investigate the impact of Laissez-faire, Transactional and Transformational leadership on employees’ motivation level. The result showed that Transformational leadership has a significant impact on the motivation level of employees in ICT sector in Nepal, while the same could not be said in the case of Laissez-faire and Transactional leadership styles.